PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN MENJAHIT DALAM PENINGKATAN KREATIVITAS REMAJA PUTRI PEKANBARU - Nelsi Arisandy (Jurnal Pengabdian Kompetitif, 2026)
Sewing is a basic skill that must be possessed by Fashion Design graduates from SMKN 4 Pekanbaru. This training is an internship collaboration with the An-Nisa 'Collection Sewing House as instruktur for 3 months involving students and teachers at SMKN 4 Pekanbaru. The method used in this service is PAR (Participatory Action Research) with hands-on practice. This training starts with the introduction of sewing tools, measurements, pattern making, cutting, sewing and finishing. The purpose of this service is to produce reliable designers so that they can help the family's economy in the future. The results of the apprenticeship are making skirts, shirts and pants and being proficient in using machines related to sewing